CONSUMO ALIMENTAR DE IDOSOS DO MEIO RURAL DE IJUÍ, RS - ROST, DÉBORA; BATTISTI, IARA D. E.; SCHWEIGERT, INGRID D.; BEIER, LIÉGE L.; DALLEPIANE, LOIVA B.; MACHADO, LUCIELE D. L.; BELLÉ, TÂNIA R. L. (Salão do Conhecimento, 2013)
Resumo